Assessment of flood simulation accuracy: comparative analysis of HEC-RAS with lidar and sentinel-1A data / Putri Evanazeha Ibrahim - Ibrahim, Putri Evanazeha (2024)
This dissertation presents a comprehensive study of flood simulation using HECRAS using LiDAR and Sentinel-1A data. The research also used data from hydrological records, Digital Elevation Models (DEMs), and topographic maps. This study uses HEC-RAS software for flood simulation and it starts by generating a DEM from satellite data using the SNAP software discussed in Chapter 3. The main objective is to analyse the flood simulation for Sungai Buloh using HEC-RAS software. The main findings highlight the exposed lowlying areas near the river especially in places such as Paya Jaras and Kg. Kubu Gajah, where significant flood depths underscore the need for targeted flood management strategies. This research emphasizes the important role of highresolution DEMs in accurately mapping floodplain boundaries for accurate flood simulations. Methodologically, this study involves steps such as initial DEM generation from satellite data using SNAP software, further refinement in ArcGIS for accurate topographic representation and improvement through LiDAR data analysis at lm x lm resolution for better accuracy. The subsequent simulation process includes digitizing the river geometry, creating cross-sections at 100m intervals, and analysing flood simulation results such as water surface profiles, flow velocities and flood maps using HEC-RAS and ArcGIS tools. Detailed flood maps are generated to identify vulnerable areas. Simulation results are carefully verified against observed data, comparing with historical flood records to ensure reliability. The study concludes with an adapted flood management strategy for Sungai Buloh and emphasizes the importance of highquality input data such as high-resolution DEM and accurate hydrological parameters in improving the accuracy of flood simulations and management effectiveness.